BOOK REVIEW OF THE OLD MAN AND THE SEA WRITTEN BY ERNEST HEMMINGWAY - Lee, Mounsu (LANTERN (Journal on English Language, Culture and Literature), 2015)
Book Review of The Old Man and the Sea by Ernest Hemingway is to understand strengths and weaknesses. This analysis uses literature methods, which are intrinsic as analysis focus. The intrinsic aspects are character, setting, conflict and theme. The results of this analysis are strengths and weaknesses. The author, Earnest Hemingway developed the story with the main character, Santiago. The story is developed by Santiago’s journey and conflicts happened through Santiago’s journey. In addition to this, Santiago gives the writer’s message in the novel. Santiago’s inner conflict and social conflict lead us to lesson of the book. Although this story is too simple, which can make readers feel bored to understand the book, the book implies many lesson and morals for who are living in modern society.Keywords: understanding strengths and weaknesses